Application of X-Ray Computed Tomography in Monitoring Chloride Ion Penetration Paths in Recycled Aggregate Concrete - Yuan Zuo; Bing Qi; Jianming Gao; Weibin Li (Advances in Materials Science and Engineering)
The penetration paths of chloride ions in recycled aggregate concrete (RAC) are of significant interest and have not been well studied previously. This study used X-ray computed tomography (X-CT) as a novel approach to investigate chloride ion penetration paths in RAC. The results indicate that X-CT can be used for the constant monitoring of chloride ion penetration paths in RAC, and the influence of mix proportions on the chloride ion penetration can be understood through the X-CT visualization.